The physiological effects of nutritional thiol supplementation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sport and Exercise Science at Massey University, Manawatu, New Zealand - McLeay, Yanita Dawn (Massey University, 2018)
Endogenous antioxidant defence systems are largely comprised of thiol antioxidants and antioxidant enzymes. Keratin protein, being high in cysteic acid, has potential to improve antioxidant status via generation of several thiol antioxidants. Common dietary antioxidants are often used by athletes aiming to reduce oxidative stress, which in turn can improve exercise performance. However, whilst studies into their action against oxidative stress are positive, the subsequent effect on exercise performance is less so. In addition to having little effect on acute performance, their non-‐specific ROS-‐targeting mechanisms may also blunt important adaptation signalling pathways. It has been proposed that improving endogenous defence systems may be of greater benefit to athletic performance, thus keratin may be an alternative to dietary antioxidant supplementation. The first study within this thesis found acute keratin supplementation to improve plasma total thiol content, while longer term supplementation increased lean body mass significantly more than casein protein. Study two suggested one week of keratin vs. taurine supplementation did not affect plasma total thiol content, while study three found that despite no significant effects on serum total thiol content, taurine improved muscle recovery following eccentric-‐induced muscle damage compared to a placebo. In summary, findings from this thesis suggest keratin may be a useful supplement for athletes wanting to maintain or gain lean body mass. This suggests implications for the use of keratin beyond athletes, potentially benefiting other population groups including the elderly and the sick. Results also suggest that supplementing with taurine following resistance exercise involving eccentric actions may improve recovery and subsequent performance. This research sets a platform for further investigation into the use of keratin and thiols for various areas of sporting performance.
Keywords: Athletes -- Nutrition; Oxidative stress -- Prevention; Antioxidants -- Physiological effect; Dietary supplements -- Physiological effect; Keratin; Taurine